BGer 2C 1165/2014 vom 3. April 2017 - Bundesgericht (2017)
Grundstückgewinnsteuer [2C_1148/2015] Impôt cantonal et communal 2012 [2C_1165/2014] Impôt fédéral direct 2012 [2C_1166/2014] | Finances publiques & droit fiscal